Pengembangan Sistem Irigasi Cerdas Bertenaga Surya dengan Monitoring Kelembaban Tanah untuk Pertanian Berkelanjutan - Purnomo Purnomo; Sahabman Tua Pardamean Naibaho; Nabila Adelia Putri; Muhammad Fadhil Dzaki (Universitas Muhammadiyah Metro, 2026)
Water availability is essential for agricultural productivity in Indonesia, especially in addressing climate change and the inefficiency of conventional irrigation systems. This study presents the design and testing of a solar-powered smart irrigation system that integrates Internet of Things (IoT) technology for efficient and sustainable water management. The system consists of an Arduino Uno, YL-69 soil moisture sensor, YF-S201 water flow sensor, 12V DC pump, and a 120 Wp solar panel as an independent energy source. It operates automatically by activating the pump when soil moisture falls below a set threshold and stopping it when optimal moisture is achieved. Test results show that the YL-69 sensor effectively detects soil moisture levels ranging from 31–81%RH, with an average increase of 40.6%RH after irrigation. The YF-S201 sensor demonstrated high accuracy with an average flow rate of 20 L/min and an error rate of only 0.89%. The pump operated steadily with an average current of 6.34A and power of 74.2W, while the solar panel produced an average of 11.88V and the battery 11.64V. Overall, the system efficiently optimizes water and energy use, supporting sustainable agriculture. Future improvements should focus on increasing battery capacity and calibrating the soil moisture sensor for more stable and accurate performance.